Effectiveness of Life Skills Training on Mental Health of Spouses of Veterans with Affective Disorders - M. Mohamadipoor; M. Falahati (Afarand Scholarly Publishing Institute, 2016)
Aims: The spouses of the veterans suffering bad situtations due to the physical and mental problems of the veterans are in mental risks in turn and with no suitable quality of life. It seems that some educations can enhance their quality of life and reduce their mental pressures. The aim of this study was to investigate the effectiveness of life skills trainings on mental health of the spouses of the veterans with mood disorders. Instrument & Methods: In the pretest-posttest semi-experimental study with a control group, 50 spouses of the veterans with mood disorders referred to Tehran Sadr Psychiatric Hospital were studied in 2013.The subjects were selected via available sampling method, randomly devided into two groups including experimental and control groups. Data was collected using a demographic questionnaire and general health questionnaire (GHQ-28). Ten 120-minute life skills training sessions were weekly conducted in experimental group. Data was analyzed using covariance analysis test.    Findings: There was a significant difference between the groups in the posttest stage with pretest effects controlling in the mean scores of life skills in general health and sub-sclaes including physical symptoms, anxity symptoms, and defects in the social functionnings (p<0.05). Nevertheless, there was no significant difference in the depression symptoms subscale (p>0.05).   Conclusion: Life skills trainings can enhance general health (physical symptoms, anxiety symptoms, and defects in the social functionnings) of the spouces of the veterans with mood disorders.